Psychophysiological, behavioral, and cognitive indices of the emotional response: a factor-analytic study - Sánchez-navarro, Juan Pedro; Martínez-selva, José María; Román, Francisco; Torrente, Ginesa (The Spanish Journal of Psychology, 2008)
Previous research on the components of the emotional response employing factor analytic studies has yielded a two-factor structure (Lang, Greenwald, Bradley, & Hamm, 1993; Cuthbert, Schupp, Bradley, Birbaumer, & Lang, 2000). However, the startle blink reflex, a widely employed measure of the emotional response, has not been considered to date. We decided to include two parameters of the startle reflex (magnitude and latency) in order to explore further how this response fits into the two-factor model of emotion. We recorded the acoustic startle blink response, skin conductance response, heart rate, free viewing time, and picture valence and arousal ratings of 45 subjects while viewing 54 pictures from the International Affective Picture System (IAPS; 18 unpleasant, 18 neutral, and 18 pleasant). Factorizations of all measures gave a two-factor solution (valence and arousal) that accounted for 70% of the variance. Although some measurements, including heart rate change, did not behave as predicted, our results reinforce the two-dimension model of the emotion, and show that startle fits into the model.